1991
DOI: 10.2355/isijinternational.31.254
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new mold oscillation mode for high-speed continuous casting of steel slabs.

Abstract: High-speed oontinuous casting is a prerequisite for the successful operation of hot direct rolling (HDR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 0 publications
5
72
0
7
Order By: Relevance
“…8. 33) Both the observed and the predicted frictional force are adopted at the maximum relative speed between the mold oscillating speed and the casting speed. Accordingly, the frictional force calculated from Eq.…”
Section: Upper Limit Of Casting Speed Of Continuous Castermentioning
confidence: 99%
“…8. 33) Both the observed and the predicted frictional force are adopted at the maximum relative speed between the mold oscillating speed and the casting speed. Accordingly, the frictional force calculated from Eq.…”
Section: Upper Limit Of Casting Speed Of Continuous Castermentioning
confidence: 99%
“…The figures themselves need a physical explanation. As stated in the introduction, also (Suzuki et al, 1991), (Araki & Ikeda, 1999), increasing τ reduces peak friction as also the depth of oscillation marks. Thus τ contributes negatively to these circles.…”
Section: Oscillation Performance Metricsmentioning
confidence: 96%
“…Only the oscillation frequency f and amplitude a or s (stroke; s = 2a) are available. Suzuki and others (Suzuki et al, 1991) showed that the waveform could also be varied from the sinusoidal towards the saw-tooth form with gainful effects. Slower…”
Section: Introductionmentioning
confidence: 99%
“…Uma delas possivelmente de alumina (1) e outra um complexo de alumina e zircônia (2). Os resultados obtidos mostram que as técnicas desenvolvidas fornecem informações confiáveis para a otimização dos parâmetros de oscilação do molde.…”
Section: Tempo De Estripamento Negativo [S]unclassified